2010
DOI: 10.1002/ls.132
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of hydrogen bonding in polypropylene glycol at EHL contact region

Abstract: In the present work, the stabilisation of hydrogen bonding of polypropylene glycol at elastohydrodynamic lubrication (EHL) contact was investigated by in situ observation with a micro-Fourier transform infrared spectrometer, and the effect of hydrostatic pressure on infrared (IR) spectra was confi rmed using a diamond anvil cell. Polypropylene glycols with different molecular weights were used as sample oils. Polypropylene glycol molecules interact with themselves by hydrogen bonding with their hydroxyl groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This result demonstrates the pressure and temperature response of the hydrogen bonding of lubricant molecules, which suggests change of molecular interaction. In past study, it was found that the peak position of the O–H stretching mode in PPG and the C═O stretching mode in OA were shifted to a lower wavenumber at the Hertzian contact region …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This result demonstrates the pressure and temperature response of the hydrogen bonding of lubricant molecules, which suggests change of molecular interaction. In past study, it was found that the peak position of the O–H stretching mode in PPG and the C═O stretching mode in OA were shifted to a lower wavenumber at the Hertzian contact region …”
Section: Resultsmentioning
confidence: 94%
“…The O–H stretching mode at 3480 cm −1 and the C═O stretching mode at 1735 cm −1 are related to the associated structure formed by hydrogen bonding . The O–H stretching mode of base oil shows the interaction between OH groups . The C═O stretching mode of OA consists of two peaks, the major peak at 1735 cm −1 as a monomer interacted with base oil and the minor peak at 1712 cm −1 as a dimmer interacting with itself, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-Fourier transform infrared spectrometry (micro-FTIR) is useful for the in situ observation of a lubricant film under elastohydrodynamic lubrication (EHL) conditions. In previous studies, several tribological phenomena at the contact point were investigated, such as the change in concentration of components [2], molecular orientation [3], and molecular interactions [4]. The results demonstrated that tribological performance was closely related to the structure of the lubricant film at the contact point.…”
Section: Introductionmentioning
confidence: 96%
“…Infrared (IR) absorption spectroscopy [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and Raman spectroscopy [16][17][18] are particularly attractive tools for studying buried interfaces nondestructively. There are many practical and interpretational problems associated with the application of Raman and IR spectroscopy to in-contact studies.…”
Section: Introductionmentioning
confidence: 99%